Curing vector for IncI1 plasmids and its use to provide evidence for a metabolic burden of IncI1 CTX‐M‐1 plasmid pIFM3791 onKlebsiella pneumoniae. Issue 7 (July 2016) - Freire Martín, Irene; Thomas, Christopher M.; Laing, Emma; AbuOun, Manal; La Ragione, Roberto M.; Woodward, Martin J.
Abstract : N/A: Using a sequence‐based approach we previously identified an IncI1 CTX‐M‐1 plasmid, pIFM3791, on a single pig farm in the UK that was harboured by Klebsiella pneumoniae, Escherichia coli and Salmonella enterica serotype 4, 5, 12:i:‐. To test the hypothesis that the plasmid had spread rapidly into these differing host bacteria we wished to assess whether the plasmid conferred a fitness advantage. To do this an IncI1 curing vector was constructed and used to displace the IncI1 CTX‐M‐1 plasmids from K. pneumoniae strain B3791 and several other unrelated IncI1‐harbouring strains indicating the potential wider application of the curing vector. The IncI1 CTX‐M‐1 plasmid was reintroduced by conjugation into the cured K. pneumoniae strain and also a naturally IncI1 plasmid free S. enterica serotype 4, 5, 12:i:‐, S348/11. Original, cured and complemented strains were tested for metabolic competence using Biolog technology and in competitive growth, association to mammalian cells and biofilm formation experiments. The plasmid‐cured K. pneumoniae strain grew more rapidly than either the original plasmid‐carrying strain or plasmid‐complemented strains in competition experiments. Additionally, the plasmid‐cured strain was significantly better at respiring with L‐sorbose as a carbon source and putrescine, γ‐amino‐n‐butyric acid, L‐alanine and L‐proline as nitrogen sources. By contrast, no differences in phenotype were found when comparing plasmid‐harbouring and plasmid‐free S. enterica S348/11. In conclusion, the IncI1 curing vector successfully displaced multiple IncI plasmids. The IncI1 CTX‐M1 plasmid conferred a growth disadvantage upon K. pneumoniae, possibly by imposing a metabolic burden, the mechanism of which remains to be determined.